Conference Scene: Highlights from the San Antonio Breast Cancer Symposium 2012. (March 2013) - Mortimer, Joanne; Kunkler, Ian; Webber, Victoria
At the San Antonio Breast Cancer Symposium 2012, long-term follow-up data from large clinical trials support a change in practice for the use of sentinel node mapping after neoadjuvant therapy and the safety and efficacy of hypofractionated radiation therapy. The duration of adjuvant therapy was further defined, with advantages reported with the extended use of adjuvant tamoxifen for 10 years and for 12 months of adjuvant trastuzumab.